Rock Art Conservation and Geotourism: A practical example from Foum Chenna engravings site, Morocco - Mohamed Abioui; Lhassan M Barki; Mohammed Benssaou; Abdelkrim Ezaidi; Nezha El Kamali (Geoconservation Research)
The rock engravings, the subject of this article, are artistic representations made by people from cultural communities who no longer exist. The rock art was a way of expressing their thoughts, culture and beliefs, before the invention of writing. The engravings represent an archive of an ancient civilization which developed over thousands of years throughout North Africa, from the Atlantic to Egypt and from the Atlas Mountains to the Sahel. Morocco has more than 300 listed rock art sites, scattered throughout the country. Foum Chenna is a major site in the Anti-Atlas Mountains of southern Morocco. The engravings were predominantly made by pecking out images of human figures, animals and patterns, and the area today is the center of interest for the recently-formed Association of Rock Art Heritage of Southern Morocco, based in Zagora. Foum Chenna is a place of primary importance with more than 800 schematic engravings made using the pecked technique, a characteristic of this period. The majority of engravings which depict riders associated with zoomorphic and anthropomorphic representations, also, importantly, the numerous rock inscriptions recounting a scriptural tradition and reflecting the historical beginnings of Libyan writing, were today revitalized to transcribe the Tamazight language. The need to study and protect this heritage should not be limited to the preserve of just a few specialists. Knowledge of it can be used, with care, for sustainable human development. The rock art and other featuresmay make the region worthy of international recognition by UNESCO. In this paper, we look at Foum Chenna site from the perspective of geotourism and importance of the site for geoeducation, and the value of Foum Chenna site as geosite. Besides, soils, considered as some of the extraordinary manifestations of the culture of the Foum Chenna, are of huge scientific importance.